Event-based neuromorphic systems - Liu, Shih-Chii; Delbruck, Tobi; Indiveri, Giacomo; Whatley, Adrian, editor; Douglas, Rodney (Chichester, West Sussex, United Kindgom : John Wiley & Sons Ltd, 2015)
Includes bibliographical references and index